The Potential Role of Neuroplasticity in the Treatment of Paraneoplastic Neuropathy with Scrambler Therapy - Murphy , Tyler K. (Current Progress in Medicine and Medical Research Vol. 9, 2023)
With an incidence of up to 8%, paraneoplastic syndromes are relatively uncommon, but are an often frustrating sequela for cancer patients with significant implications on quality of life [1] Paraneoplastic sensory neuropathic syndromes are among the more common paraneoplastic syndromes, and can present in a variety of ways including pain, numbness, and/or pruritus. It can be a particularly difficult condition to manage as it often does not resolve even with successful treatment of cancer. Scrambler Therapy is a non-invasive neuromodulation therapy that is believed to replace the pain signals involved in neuropathic syndromes with “non-pain information” through the process of neuroplasticity. Scrambler Therapy is approved for chronic and neuropathic pain, and has been shown to have few, if any, side effects. We report here a case of paraneoplastic neuropathy, presenting with pain and pruritus, that responded to Scrambler Therapy without side effects or complications.